2018
DOI: 10.1063/1.5031767
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of turbulence decay in dense suspensions using index-matched hydrogel particles

Abstract: In the present study, a refractive-index matching (RIM) technique using hydrogel particles was developed to quantitatively measure turbulence characteristics in dense suspensions. Compared to classic RIM methods, the use of superabsorbent polymer (SAP) material significantly simplifies experimental procedures and avoids strict experimental controls, which makes the method particularly suitable for turbulence measurements in dense suspensions. Because of the high absorbency of the approximately 1 mm SAP particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…The current study extends its analysis of depletion efficiency to dilute and dense suspensions by using a refractive index matching technique (Wiederseiner et al 2010). Recently, studies using super-absorbent hydrogel beads of various diameters have demonstrated turbulence attenuation and vortex formation dynamics in dense suspensions with volume fractions up to 25 % (Zhang & Rival 2018;Baker & Coletti 2019;Zhang & Rival 2020). However, much is still unknown about the contribution of the suspended phase in the entrainment process of pulsatile recirculating flows.…”
Section: Steady Versus Pulsatile Flowsmentioning
confidence: 79%
See 1 more Smart Citation
“…The current study extends its analysis of depletion efficiency to dilute and dense suspensions by using a refractive index matching technique (Wiederseiner et al 2010). Recently, studies using super-absorbent hydrogel beads of various diameters have demonstrated turbulence attenuation and vortex formation dynamics in dense suspensions with volume fractions up to 25 % (Zhang & Rival 2018;Baker & Coletti 2019;Zhang & Rival 2020). However, much is still unknown about the contribution of the suspended phase in the entrainment process of pulsatile recirculating flows.…”
Section: Steady Versus Pulsatile Flowsmentioning
confidence: 79%
“…The mean inter-particle spacing, normalized by the bead diameter, is l p /d p ≈ 2.3, 1.9 and 1.5 for the Φ = 5 %, 10 % and 20 % suspensions, respectively, where l p is the centre-to-centre distance between hydrogel beads and l p /d p ≤ 2 for dense suspensions (Kryuchkov 2001). The settling velocity of the hydrogel beads has previously been measured at approximately 0.6 ± 0.3 mm s −1 (Zhang & Rival 2018) and is very low when compared to the convective speeds of the system. Furthermore, the concentration of beads in the current tested suspensions is sufficiently high that these particles cannot be considered to move (settle) in isolation of one another.…”
Section: Hydrogel Beads -Making a Dense Suspensionmentioning
confidence: 99%
“…The aforementioned PIV measurement technique that renders suspensions optically transparent was first demonstrated by Zhang & Rival (2018). In that study, a velocity uncertainty of 0.33 pixels was obtained for measurements taken through approximately 85 particle–fluid interfaces.…”
Section: Experiments Set-upmentioning
confidence: 99%
“…Additionally, we compare the dynamics of vortex rings in dense suspensions with those formed in pure water at low Reynolds numbers (Palacios-Morales & Zenit 2013), since the effective viscosity typically increases in suspensions. We implement refractive index matched hydrogel particles to produce optically transparent suspensions (Zhang & Rival 2018), which enables the use of time-resolved particle image velocimetry (PIV) measurements to quantify the velocity and vorticity fields of the liquid phase. This method has also been successfully applied to measure the solid and liquid phases of confined vortex rings simultaneously in suspensions using shake-the-box measurement techniques (Zhang, Jeronimo & Rival 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in numerical algorithms and computer technology enables researchers to examine the behavior of individual particles in great detail in suspensions even at high solid volume fractions (Kazerooni et al 2017). Nonetheless, only a few experimental studies address the individual particle dynamics in suspensions beyond the dilute regime by means of optical measurement techniques such as Particle Image Velocimetry (PIV) (Zade et al 2018(Zade et al , 2019Zhang and Rival 2018) or a combination of PIV and 2D Particle Tracking Velocimetry (PTV) (Baker and Coletti 2019). Optical measurement techniques have been proven to be reliable tools for investigating fluid flow problems with high spatial and temporal resolutions.…”
Section: Introductionmentioning
confidence: 99%